2017
DOI: 10.1186/s12889-017-4296-6
|View full text |Cite
|
Sign up to set email alerts
|

Beyond efficacy in water containers: Temephos and household entomological indices in six studies between 2005 and 2013 in Managua, Nicaragua

Abstract: BackgroundA cluster-randomized controlled trial of community mobilisation for dengue prevention in Mexico and Nicaragua reported, as a secondary finding, a higher risk of dengue virus infection in households where inspectors found temephos in water containers. Data from control sites in the preceding pilot study and the Nicaragua trial arm provided six time points (2005, 2006, 2007 and 2011, 2012, 2013) to examine potentially protective effects of temephos on entomological indices under every day conditions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The documented preference of mosquitoes to feed on larger targets (36)(37)(38), the trend analysis, and the extended risk factor analysis all suggest that the large and continual increases in BSA during childhood and adolescence are primarily responsible for the sharp rise in ZIKV seroprevalence during that period. Aedes mosquitoes, the only known vectors for arboviruses in Nicaragua (46), are attracted to carbon dioxide and other components associated with human respiration and perspiration, which aid female Aedes mosquitoes in locating a blood meal (36,47). Larger and heavier persons expel more of these attractive components, explaining, together with exposed skin surface area, the general trend for older individuals to have a higher seroprevalence than younger individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The documented preference of mosquitoes to feed on larger targets (36)(37)(38), the trend analysis, and the extended risk factor analysis all suggest that the large and continual increases in BSA during childhood and adolescence are primarily responsible for the sharp rise in ZIKV seroprevalence during that period. Aedes mosquitoes, the only known vectors for arboviruses in Nicaragua (46), are attracted to carbon dioxide and other components associated with human respiration and perspiration, which aid female Aedes mosquitoes in locating a blood meal (36,47). Larger and heavier persons expel more of these attractive components, explaining, together with exposed skin surface area, the general trend for older individuals to have a higher seroprevalence than younger individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of effect is possibly caused by negligence in eliminating breeding sites observed in the group that also applied temephos and the dilution of the insecticide in non-removable containers. A study in Nicaragua also did not demonstrate a positive effect of temephos combined with other interventions [ 110 ]. In the mentioned study, temephos exposure was not associated with a reduction in any entomological indices, and in some cases, temephos exposure was even associated with higher entomological outcomes [ 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…In previous analyses, we found that three variables were significant predictors of vector density: use of abate during the past 30 days, regularity of water access, and participation in organizations. 34,44 We attempted to balance these variables between our intervention and control neighborhoods, as well as neighborhood size; therefore, we measured the level of each variable at 18 months in all neighborhoods. There was no significant difference in water access (P 5 0.7262) and participant organization (P 5 0.442).…”
Section: Community-based Arbovirus Vector Controlmentioning
confidence: 99%